Simulation of stationary, non-normal random process - Menh, Nguyen Cao; Tri, Tran Duong (Vietnam Journal of Mechanics, 1992)
Simulation of stationary random processes specified by spectral density function and NonNormal probability density function has been rarely studied, though these processes are often met in both theory and practice. In this paper we consider a simulation method which can apply to the mention-above processes. The main idea based on the simulation of the Normal process and approximation of functions in the space of quadratic ally integrable functions. The numerical program for illustration of the method is written by Turbo - Pascal language.